1984
DOI: 10.1007/bf01711378
|View full text |Cite
|
Sign up to set email alerts
|

25-hydroxyvitamin D, 24, 25-dihydroxyvitamin D and 1,25-dihydroxyvitamin D in human cerebrospinal fluid

Abstract: Samples of CSF and plasma were obtained simultaneously from 46 adult patients who had no endocrine disorders and were undergoing routine diagnostic lumbar puncture because of suspected or proved prolapse of a disc. Concentrations of 25-OHD, 24,25(OH)2D and 1,25(OH)2D were measured. The samples were purified by column chromatography and fractionated by HPLC. In the appropriate fractions the vitamin D metabolites were measured by PBA, and cytoreceptor assay. The results were as follows (median, range in brackets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
6

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 30 publications
1
50
1
6
Order By: Relevance
“…Alterations in glucose utilization are known to occur in the important regions of brain connected with learning and memory [64]. Learning and memory processing is found to produce increases of glucose metabolism in the cortical brain regions that is functionally related to memory processing as well as to the sensorimotor task requirements [65,66]. Our findings suggest a modulation of GLUT 3 expression in the brain with Vitamin D 3 supplementation which consecutively normalise the glucose transport in brainstem.…”
Section: Discussionmentioning
confidence: 70%
“…Alterations in glucose utilization are known to occur in the important regions of brain connected with learning and memory [64]. Learning and memory processing is found to produce increases of glucose metabolism in the cortical brain regions that is functionally related to memory processing as well as to the sensorimotor task requirements [65,66]. Our findings suggest a modulation of GLUT 3 expression in the brain with Vitamin D 3 supplementation which consecutively normalise the glucose transport in brainstem.…”
Section: Discussionmentioning
confidence: 70%
“…Evidence for a role of vitamin D in brain function began to accumulate over two decades ago with autoradiographic findings of vitamin D receptors in the brains of experimental animals (Stumpf, Sar et al 1982) and the demonstration that 1,25(OH) 2 D 3 was present in cerebrospinal fluid (Balabanova, Richter et al 1984). Animal studies revealed the presence of VDR in the neuroepithelium during early neurogenesis, and in later stages, in an area involved in the maintenance of neural stem cells, the subventricular zone (Veenstra 1998).…”
Section: Vitamin D and The Brain: Mechanisms Of Actionmentioning
confidence: 99%
“…The discovery of vitamin D metabolites in the cerebrospinal fluid offered the first direct clue of its functional role in the nervous system (Balabanova et al 1984).…”
Section: Vitamin D and Neurodevelopmentmentioning
confidence: 99%